Lactate vs pedalling in BMX cycling discipline - Mateo March, M.; Blasco-Lafarga, C.; Zabala Diaz, M.; Guzmán Luján, J. F.; Velarde Ganivet, S.; Simón Castro, A.; Oviedo Durá, A. (Archivos de medicina del deporte, 2008)
Introduction: Traditionally, BMX is considered an Anaerobic Power and cyclic sport (mean time in Offi cial Championships: 34.66±2.39 s). However, this discipline has important technical requirements of skill and strength that disrupt and diminish the pedalling, and moreover, the few BMX published papers refl ect low concentrations of lactate (8.55 ± 3.74 mMol/l). This study aims to deepen on the BMX lactate values, its meaning and its possible relationship with the skills used in competition. Materials and methods: An experimental design was carried out with two intrasubject variables; the first was the type of track, with three items: 1) high diffi culty, 2) medium difficulty and 3) low difficulty. The second one was the technical determining factor (pedalling, Figure 1), with three items: 1) Non-pedalling race, 2) pedalling only on the Gate Start, and 3) competition pedalling. 10 athletes, 8 men and 2 women from the Spanish Junior Team, made 9 races, three on each circuit and on each technical condition; next to an anthropometry. Blood lactate was measured after each test. Results: The results on the Analysis of Variance for repeated measures showed no statistical differences according to the greater or lower possibility of pedalling, while we found the maximum signifi cance according to the track (p <.001); therefore, regarding to the technical difficulty lactate levels were significantly higher as technical difficulty decreased. This significance is kept when analysing the interaction pedalling*track (p =. 025). Conclusions: The highest the technical diffi culty, the lowest the lactate concentration; while in the less technical tracks pedalling becomes more signifi cant in performance, resulting lactates signifi cantly higher. The data support the hypothesis that the BMX has components of skill and force that become more determinant when increasing the technical level (most difficult tracks), making it necessary to complete the performance assessment with other more neuromuscular variables.